The Legal Validity of Oral Agreements in Online Arisan Practices: Kekuatan Hukum Perjanjian Tidak Tertulis (Lisan) dalam Arisan Online - Widjanarko, Wildan Kristanto; Djumikasih; Nurhayati, Prawatya Ido (WARKAT, 2025)
This study examines the legal validity of oral agreements in electronic-based arisan practices, commonly known as “online arisan.” The issue arises due to the lack of clear and comprehensive regulations governing online arisan, despite its rapid growth in Indonesia. This regulatory gap has resulted in frequent acts of default by both organizers and participants. Although online arisan is based on contractual agreements between members and organizers, its implementation must also comply with the Electronic Information and Transactions Law (ITE Law), as the activities are carried out electronically. However, because online arisan is a relatively recent development, it has not been fully regulated under the ITE Law. Oral agreements in online arisan remain legally valid, as they meet the essential requirements for a binding contract under the Indonesian Civil Code. This is supported by Article 5(4) of the ITE Law, which affirms that online agreements do not always need to be made in writing. Nevertheless, oral agreements have limitations in evidentiary strength when disputes or breaches of contract arise. This study emphasizes the need for clearer and more detailed legal regulations to ensure legal certainty and protection for both organizers and participants in online arisan practices.